Darbiniekam radītu nelabvēlīgu seku konsekvences un prevencija - Nesaule, Ilze (Latvijas Universitāte, 2013)
Darbs veikts ar mērķi aizliegumu radīt darbiniekam nelabvēlīgas sekas par tā tiesību izmantojumu no deklaratīvas tiesību normas pārvērst par efektīvu darbinieka tiesību aizsardzības instrumentu. Darbā identificēti problēmjautājumi normatīvajā regulējumā, tā iztulkošanā un piemērošanā, izstrādāti priekšlikumi trūkumu novēršanai. Tādēļ skaidrots minētā tiesību institūta saturs, analizēta situācija darba attiecību un tiesvedības ietvaros. Darba rezultātā ierosināts pilnveidot aizlieguma radīt nelabvēlīgas sekas normatīvo regulējumu: 1) saskaņojot tā terminoloģiju un izvietojumu Darba likuma 9.panta, Darba likuma, civiltiesību, Eiropas Savienības tiesību ietvaros; 2) konkretizējot darbinieka izmantojamo tiesību apjomu; 3) paredzot darbinieka tiesības uzteikt darba līgumu nekavējoties; 4) ieviešot morālā kaitējuma prezumpciju; 5) koriģējot pierādīšanas procesu.

The Bachelor thesis aims to provide analyses of the prohibition to cause adverse consequences to an employee, the use of rights of it, and the possibility to transform these rights from declarative norms to effective legal instrument for protecting rights of employees. There are problematic questions within normative regulation of the prohibition to cause adverse consequences, its interpretation and application that is identified and discussed within the Bachelor thesis. The thesis proposes suggestions how to prevent these weaknesses. Therefore it explains the content of institutions of rights mentioned above, it also analyses situations of employment relationship and legal proceedings. As the result the Bachelor thesis suggests how to improve the legal regulation of the prohibition to cause adverse consequences: 1) make the meaning of its terminology more precise and concretize its location within section 9th of Labour Law, Labour Law in general, within civil rights and rights of EU; 2) concretize the extent of rights used by employees; 3) accepting rights of employees to give notice of termination immediately; 4) introducing presumption of moral harm; 5) correcting the process of its proof.
The effects of prohibition to cause adverse consequences to an employee and its preventions
Keywords: Juridiskā zinātne